2018
DOI: 10.2147/cmar.s167424
|View full text |Cite
|
Sign up to set email alerts
|

Targeting energy metabolism to eliminate cancer cells

Abstract: Adaptive metabolic responses toward a low oxygen environment are essential to maintain rapid proliferation and are relevant for tumorigenesis. Reprogramming of core metabolism in tumors confers a selective growth advantage such as the ability to evade apoptosis and/or enhance cell proliferation and promotes tumor growth and progression. One of the mechanisms that contributes to tumor growth is the impairment of cancer cell metabolism. In this review, we outline the small-molecule inhibitors identified over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 99 publications
0
13
0
2
Order By: Relevance
“…During the last decade, a great attention has also been paid to energy metabolic reprogramming of cancer. However, cancer basic studies fail to reach a consistent conclusion on mitochondrial function in cancer energy metabolism [ 21 ]. The mtDEPs enriched in mitochondrial dysfunction pathway (Supplementary Figure 1 item 2) provided molecular markers of the abnormal energy metabolism between cancer tissues and control tissues, including ACO1 (fold change = 0.65, p = 0.006), AIFM1 (fold change = 1.58, p = 0.002), ATPAF1 (fold change = 1.90, p = 0.009), ATPAF2 (fold change = 1.54, p = 0.0001), BCL2 (fold change = 0.30, p = 0.00003), COX17 (fold change = 2.74, p = 0.004), COX4I1 (fold change = 1.51, p = 0.004), COX4I2 (fold change = 0.20, p = 0.0006), COX6C (fold change = 1.54, p = 0.005), COX7A2 (fold change = 1.54, p = 0.03), COX7A2L (fold change = 1.87, p = 0.005), CYCS (fold change = 2.42, p = 0.001), GPX7 (fold change = 1.66, p = 0.0002), HTRA2 (fold change = 1.57, p = 0.008), MAOB (fold change = 0.41, p = 0.0002), TXN2 (fold change = 1.52, p = 0.005), and UQCRH (fold change = 1.59, p = 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…During the last decade, a great attention has also been paid to energy metabolic reprogramming of cancer. However, cancer basic studies fail to reach a consistent conclusion on mitochondrial function in cancer energy metabolism [ 21 ]. The mtDEPs enriched in mitochondrial dysfunction pathway (Supplementary Figure 1 item 2) provided molecular markers of the abnormal energy metabolism between cancer tissues and control tissues, including ACO1 (fold change = 0.65, p = 0.006), AIFM1 (fold change = 1.58, p = 0.002), ATPAF1 (fold change = 1.90, p = 0.009), ATPAF2 (fold change = 1.54, p = 0.0001), BCL2 (fold change = 0.30, p = 0.00003), COX17 (fold change = 2.74, p = 0.004), COX4I1 (fold change = 1.51, p = 0.004), COX4I2 (fold change = 0.20, p = 0.0006), COX6C (fold change = 1.54, p = 0.005), COX7A2 (fold change = 1.54, p = 0.03), COX7A2L (fold change = 1.87, p = 0.005), CYCS (fold change = 2.42, p = 0.001), GPX7 (fold change = 1.66, p = 0.0002), HTRA2 (fold change = 1.57, p = 0.008), MAOB (fold change = 0.41, p = 0.0002), TXN2 (fold change = 1.52, p = 0.005), and UQCRH (fold change = 1.59, p = 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Modulating ATP availability might be an essential strategy in inducing cell resistance and sustaining cancer progression and growth (4). Recent findings have demonstrated that cancer cells take advantage of high OXPHOS, including leukemias, lymphomas, pancreatic ductal adenocarcinoma, melanoma, and endometrial carcinoma (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), while mitochondria can modulate their morphology regulating the intrinsic apoptotic pathway and participating in the resistance of cancer cells to apoptotic stimuli (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…These data indicate that the reprogramming of glycogen metabolism in MPC provides a source of energy contributing to the tumor cell survival. Like other targeted therapies being developed, anticancer agents targeted on GLUT1 and glucose metabolism associated enzymes have demonstrated promising anticancer activities [36-38]. Targeting inhibition of these glycogen metabolism enzymes might warrant consideration as possible anticancer therapies in future studies for colorectal MPCs.…”
Section: Discussionmentioning
confidence: 99%